CULTURE SYSTEM IN NAAMA OASES (SOUTHWESTERN ALGERIA) - Boucherit, Hafidha; Benaradj, Abdelkrim; Mihi, Ali; Benniou, Ramdane (Economics of Agriculture, 2024)
The present study contributes to the identification of cropping systems applied to traditional argosystems in Naama region (southwest of Algeria). A series of farm surveys were conducted for 30 oases farmers using a semi-structured questionnaire on aspects related to systemic typology crops practiced in Moghrar and Tiout oases in Naama region. The obtained results showed a diversification of crops grown intensively in these oases. They are characterized by the practice of mixed food crops cultivation in underlying strata, associated with family-type livestock farming. Truly, the presence of 35 different crops: date palm cultivar, 5 forage crops, 16 market gardens and 13 fruit trees has been recorded. This oasis system represents an ancestral oasis heritage built and maintained by the local population owing to a careful management of natural resources.